Correlates of teacher performance / Abdul Shukor Shaari and Noran Fauziah Yaakub - Shaari, Abdul Shukor; Yaakub, Noran Fauziah (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2006)
Performance can be regarded as almost any behavior, which is directed toward task or goal accomplishment. An empirical investigation was made of a model for predicting teacher performance. Predictor variables included personal variables as well as job-related factors. This correlational study involved a total of 370 secondary school teachers from 108 schools in Kedah. Two dimensions that are performance by supervisors and performance by teaching achievement measured job performance. Results indicated that achievement motivation was the highest predictor for job performance.